Sistema electrónico para el control de riego y adquisición de datos en la monitorización de temperatura, humedad y luminosidad de un invernadero. - Carvajal-González, Claudio (Instituto Tecnológico de Costa Rica, 2015)
The Biotechnology Research Center "CIB" is a research group formed by professors of biology. The center is located in front of the School of Environmental Engineering in the Technological Institute of Costa Rica. It currently has a research greenhouse for studying various species, teachers in charge of these projects are faced with the problem that there is no system which can be programmed watering intervals on tables working. The CIB has decided to make a system that allows scheduling irrigation tables and sections, besides generating a history of environmental conditions at the place given by the variables temperature, humidity and light. The prototype developed in this graduation project will be implemented in the future in a new greenhouse to be constructed behind the facilities of the research center, it has set the stage for this purpose. This electronic system developed taking into account the number of tables to be installed in the new greenhouse to design a network of sensors that are distributed throughout the 8 tables and two working sections, in order to monitor more than one point in greenhouse temperature, humidity and light.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2015.
Keywords: Humedad; Linux; Temperatura; Servidores; Web; Monitoreo; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics